2020
DOI: 10.1002/pc.25636
|View full text |Cite
|
Sign up to set email alerts
|

Insulating polysiloxane coating forXLPE‐Si‐rubber interfaces with high long‐term stability

Abstract: Cable joints play an important role in the power supply systems, but at the same time, they greatly contribute to the majority of direct failures. Weak parts of the cable lines, especially for the solid‐solid interfaces in joints, attract much attention and are investigated by researchers worldwide. High‐voltage power transmission in electrical grids requires reliable and durable dielectric coatings for the interface insulation. The breakdown caused by local electric field enhancement is a gradual damaging pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Different nanofillers and concentrations have different effects on the electrical properties of the insulating materials. [12][13][14] However, the uniform dispersion of the nanofillers and their compatibility with polymeric materials are major issues. 15 Moreover, the long-term stability of nanofillers and voltage stabilizers and their possible reaction with antioxidants and crosslinking agents need rigorous research.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different nanofillers and concentrations have different effects on the electrical properties of the insulating materials. [12][13][14] However, the uniform dispersion of the nanofillers and their compatibility with polymeric materials are major issues. 15 Moreover, the long-term stability of nanofillers and voltage stabilizers and their possible reaction with antioxidants and crosslinking agents need rigorous research.…”
Section: Introductionmentioning
confidence: 99%
“…Anh et al 11 reported that adding different concentrations of nano TiO 2 reduced the breakdown voltage of LDPE. Different nanofillers and concentrations have different effects on the electrical properties of the insulating materials 12–14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the installation of cable accessories, the XLPE surface is coated with silicone grease (SG) for lubrication and sealing [17]. This SG coating has been shown to effectively increase the breakdown voltage of the XLPE–SiR interface; however, the SG can migrate into the SiR and cause swelling [18, 19]. Zhu et al showed that in addition to swelling of the SiR, the SG coating can lead to decreased hardness, tensile strength at break, and elongation at break of the SiR [20].…”
Section: Introductionmentioning
confidence: 99%